2004
DOI: 10.1002/dvdy.10439
|View full text |Cite
|
Sign up to set email alerts
|

Zinc finger protein Zac1 is expressed in chondrogenic sites of the mouse

Abstract: Zac1 is a zinc finger transcription factor that elicits antiproliferative activity and is a potential tumor suppressor gene. Through a detailed spatiotemporal study by in situ hybridization of mouse embryos, we have found that Zac1 transcript is predominantly localized in developing chondrogenic tissue, in addition to the central nervous system as reported elsewhere. Zac1 is also expressed transiently in the myocardium, skeletal muscle, and basal aspect of the stratified embryonic epithelia. During cartilage d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 26 publications
(26 reference statements)
1
23
0
Order By: Relevance
“…In situ hybridization of mouse embryos showed that Zac1 transcript is predominantly localized in developing chondrogenic tissue (Tsuda et al, 2004). Zac1 is also expressed transiently in the myocardium, skeletal muscle, and basal aspect of the stratified embryonic epithelia.…”
Section: Gene Expression During Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In situ hybridization of mouse embryos showed that Zac1 transcript is predominantly localized in developing chondrogenic tissue (Tsuda et al, 2004). Zac1 is also expressed transiently in the myocardium, skeletal muscle, and basal aspect of the stratified embryonic epithelia.…”
Section: Gene Expression During Developmentmentioning
confidence: 99%
“…Zac1 is also expressed transiently in the myocardium, skeletal muscle, and basal aspect of the stratified embryonic epithelia. During cartilage development, the pattern of Zac1 expression is closely associated with the distribution of type II collagen mRNA in mesenchymal condensation and prehypertrophic chondrocytes (Tsuda et al, 2004). In mouse ATDC5 cells undergoing in vitro chondrogenesis, the Zac1 mRNA was upregulated in parallel with genes expressed in pre-cartilage but the Zac1 expression was low when type II collagen mRNA was markedly increased in differentiated cells.…”
Section: Gene Expression During Developmentmentioning
confidence: 99%
“…4B). The Zac1 transcript is predominantly localized in developing chondrogenic tissue and suggested that Zac1 is a potential regulatory gene involved in chondrogenic differentiation and cartilage development (39,40). Overexpression of a Hoxc8 transgenic mice has been reported to cartilage defects (14).…”
Section: Ncammentioning
confidence: 99%
“…Nevertheless, their biological role in neural development and in mature brain remains uncertain. Furthermore, Zac1 and hZAC are highly expressed in somites and limbs during early embryonic stages (Piras et al, 2000;Valente and Auladell, 2001;Tsuda et al, 2004), as well as in cartilage primordium sites (Valente and Auladell, 2001;Tsuda et al, 2004) and skeletal muscle Ma et al, 2004). In adult tissues, hZAC (human homolog of Zac1 mouse gene) and Zac1 are expressed to a low extent in skeletal muscle and bone marrow (Varrault et al, 1998;Piras et al, 2000).…”
Section: Introductionmentioning
confidence: 99%